Phantasma: Wicked Games # 1 - Smith, Kaylie (New York ; Boston : Forever, 2024)
"In this spellbinding romantic fantasy, a young witch partners with a powerful ghost to save her sister-but when the competition turns deadly, his help may very well damn her instead. Phantasma only has two rules. Don't fall in love within its walls-and stay alive. When Ophelia and her sister find their mother brutally murdered, Ophelia has no time to grieve: not only has she inherited her family's magic but she is now responsible for her mother's debt. If the siblings don't come up with the money in one month, their childhood home will be demolished by the city. But when her sister recklessly tries to win the money by entering Phantasma, Ophelia cannot abandon her-even if most contestants never escape alive. No one knows how Phantasma started or who rules its terrors: the haunted competition travels from city to city, and winning is rumored to cost your soul. Ophelia, however. only wants to find her sister. But that's easier said than done. She's nowhere to be found and to Ophelia's horror, her OCD has become a new beast within the manor's haunted walls. Soon, she can't tell which terrors are her own mind and which are Phantasma's tricks to scare her away. When Ophelia meets Blackwell, she knows better than to trust him-the handsome ghost possesses powers no spirit should have. But when Blackwell offers Ophelia protection against the competition's magic in exchange for her help with a mysterious task, she has no choice but to accept. Only as Ophelia and Blackwell grow closer to gaining what they both desire, they also risk breaking Phantasma's cardinal rule . . . and soon Ophelia must decide if saving her family's legacy is worth the risk of losing herself"--.
new book 2025 summer.
Keywords: Fantasy; Horror; Romance; Paranormal fiction; Novels; Romance fiction; Fantasy fiction